Ordinary Poverty : A Little Food and Cold Storage - DiFazio, William (Book collections on Project MUSE., 2005)
At St. John's Bread and Life, a soup kitchen in the Bedford-Stuyvesant section of Brooklyn, more than a thousand people line up for breakfast and lunch five days a week. During the twelve-year era of welfare reform, William DiFazio observed the daily lives of poor people at St. John's and throughout New York City. In this trenchant and groundbreaking work, DiFazio presents the results of welfare reform - from ending entitlements to diminished welfare benefits - through the eyes and voices of those who were most directly affected by it. Ordinary Poverty concludes with a program to guara.